2009
DOI: 10.1080/00914030802639999
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical and Mechanical Properties ofHibiscus sabdariffaFiber/Polymer Composite

Abstract: Tensile, compressive, flexural and wear resistance properties of Hibiscus sabdariffa fiber-reinforced phenolic (Resorcinol Formaldehyde) resin matrixbased composites were evaluated to assess the possibility of using these fibers as a new eco-friendly material in engineering applications. Polymer composite samples were fabricated by a compression-molding technique developed in our laboratory. The effect of fiber dimension on mechanical properties was evaluated. The interfacial bonding between Hibiscus sabdariff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Cellulose is an easily available, renewable, soft and flexible fibre, hydrophilic in nature (water contact angle, WCA is 17-47°) and has very high breathability, and hence it is used in wearable materials, composites, smart textiles, adhesives, paper products, medical bandages and adsorbent materials [35,[60][61][62][63][64]. By changing, the nature of the cellulose through certain modifications, one can introduce the multifunctional properties to the cellulose fabrics.…”
Section: Cellulosementioning
confidence: 99%
“…Cellulose is an easily available, renewable, soft and flexible fibre, hydrophilic in nature (water contact angle, WCA is 17-47°) and has very high breathability, and hence it is used in wearable materials, composites, smart textiles, adhesives, paper products, medical bandages and adsorbent materials [35,[60][61][62][63][64]. By changing, the nature of the cellulose through certain modifications, one can introduce the multifunctional properties to the cellulose fabrics.…”
Section: Cellulosementioning
confidence: 99%
“…Butyl-acrylate (BA)-gSaccaharum cilliare fibers were synthesized using a redox initiator via free radical polymerization [53]. Some other studies were reported on Grewia Optiva fiber and Hibiscus sabdariffa fiber-reinforced phenol-formaldehyde (PF) composites [32][33][34][35]42] and pine needle reinforced urea-formaldehyde composites [30,31].…”
Section: Natural Polymer-based Nanocompositesmentioning
confidence: 99%
“…Polymer nanocomposites not only demonstrate substantially improved chemical and mechanical properties at much lower loading of fillers, in contrast to the conventional micron-scale fillers of polymer composites, but also possess lower component weight and have simpler processing techniques [20,76,77,[138][139][140][141][142]. Different types of polymers, composites, and nanocomposites have been used in a number of applications [124][125][126][127][128][143][144][145]. Moreover, the multifunctional enhanced properties of polymers and nanocomposites may result in new uses for polymers [49,[146][147][148][149][150].…”
Section: Introductionmentioning
confidence: 96%